Acute/baseline ratios of all 3 MC mediator metabolites can enhance diagnosis and management of mast cell activation syndrome - Joseph H. Butterfield, MD; Adela Taylor, MD (Journal of Allergy and Clinical Immunology: Global)
Background: Mast cell (MC) activation syndrome (MCAS) can be a challenge to diagnose and treat despite the near continuous appearance of publications outlining specific criteria. Follow-up of the clinical responses to treatment is often lacking, and confirmation that leukotriene C4 (LTC4) is an active participant in MCAS has been overlooked. Objective: Three patients with MCAS characterized by anaphylaxis are presented to illustrate (1) the value of contemporaneous urinary mediator sampling during MCAS in addition to serum tryptase measurements and (2) substantiation of the fact that not only can LTC4 (measured metabolite LTE4) be the highest metabolite measured, but (3) blockade of the LTE4 receptor can contribute to symptom prevention. Method: The study methods comprised clinical review and quantitation of acute and baseline levels of tryptase and urinary MC mediators. Results: The cases of 3 patients with MCAS are reviewed. In the first case, vespid sting–induced anaphylaxis was associated with a marked increase in the LTE4 excretion. The addition of montelukast was instituted, and subsequent stings did not evoke symptoms. In the second case, acute measurements showed substantial increased levels of (2,3-dinor)-11β-prostaglandin F2α, and LTE4. The addition of aspirin plus montelukast prevented subsequent attacks. The third case documents a perioperative anaphylactic event with an acute/baseline LTE4 ratio far higher than those of tryptase or other metabolites. Conclusions: The value of measuring all 3 MC mediator metabolites during MCAS should not be overlooked. These measurements can facilitate the successful prevention of attacks. Furthermore, results from these tests show that histamine is often a minor player, whereas acute/baseline levels of the metabolites of LTC4 and prostaglandin D2 are frequently much higher, warranting nonantihistamine treatment.